Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1200/jco.19.00463
|View full text |Cite|
|
Sign up to set email alerts
|

Phase II Evaluation of Aggressive Dose De-Escalation for Adjuvant Chemoradiotherapy in Human Papillomavirus–Associated Oropharynx Squamous Cell Carcinoma

Abstract: PURPOSE The purpose of this study was to determine if dose de-escalation from 60 to 66 Gy to 30 to 36 Gy of adjuvant radiotherapy (RT) for selected patients with human papillomavirus–associated oropharyngeal squamous cell carcinoma could maintain historical rates for disease control while reducing toxicity and preserving swallow function and quality of life (QOL). PATIENTS AND METHODS MC1273 was a single-arm phase II trial testing an aggressive course of RT de-escalation after surgery. Eligibility criteria inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
137
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(145 citation statements)
references
References 38 publications
2
137
0
6
Order By: Relevance
“…In the adjuvant setting, the reduction of RT dosing (to 30-36 Gy) with concurrent docetaxel resulted in comparable LRC and survival, with significant reductions of acute and late toxicities compared to reported standard therapy outcomes [70]. Similarly, sparing of RT to the primary site during adjuvant treatment found reassuring survival (100% OS, 98% 2-year recurrence-free survival [RFS]) and quality of life outcomes [71].…”
Section: Treatment De-intensification In Hpv-positive Opsccmentioning
confidence: 99%
“…In the adjuvant setting, the reduction of RT dosing (to 30-36 Gy) with concurrent docetaxel resulted in comparable LRC and survival, with significant reductions of acute and late toxicities compared to reported standard therapy outcomes [70]. Similarly, sparing of RT to the primary site during adjuvant treatment found reassuring survival (100% OS, 98% 2-year recurrence-free survival [RFS]) and quality of life outcomes [71].…”
Section: Treatment De-intensification In Hpv-positive Opsccmentioning
confidence: 99%
“…We recently reported the first prospective phase II trial of aggressive dose de-escalation of adjuvant therapy as a single institutional trial (MC1273) in an effort to rapidly investigate the efficacy of aggressive dose de-escalation. 16 Perhaps the most impactful finding from MC1273 and this comparison to standard of care adjuvant therapy is that intermediate risk patients (completely resected disease (R0), 1-4 nodes (pN1), without ENE) have a very low incidence of recurrence with both de-escalation and standard adjuvant therapy. The most important risk factors for progression were higher T stage, pN2 disease, and the presence of ENE.…”
Section: Discussionmentioning
confidence: 99%
“…An additional five eligible studies were added, including four that were published after the cut-off date of 01/10/2019 [15][16][17][18] and one randomized trial that was not identified through the literature search. 19 Studies with primary oncologic endpoints are shown in Table S1 and included 11 systematic reviews, [20][21][22][23][24][25][26][27][28][29][30] 24 randomized trials with four long-term updates, 19,31-57 29 nonrandomized clinical trials, [15][16][17][18] and nine post hoc analyses of randomized trials. [83][84][85][86][87][88][89][90][91] The randomized trials are presented in Table 4.…”
Section: Characteristics Of Studies Identified In the Literature Sementioning
confidence: 99%
“…16,18 A recent phase II study of 80 patients with HPV-mediated oropharynx SCC showed a 2-year PFS and LRC of 91.1% and 96.2%, respectively, with a postoperative regimen of 30 Gy given at 1.5 Gy twice daily with a simultaneous integrated boost of 1.8 Gy BID to areas of ENE (total dose 36 Gy) and concurrent weekly docetaxel 15 mg/m 2 . 16 The ECOG 3311 phase II clinical trial has completed followup and will determine the efficacy of reduced-dose PORT (50 Gy) compared to standard PORT (60 Gy) for patients with intermediate-risk cancers, negative margins, and ≤1 mm extranodal extension (NCT01898494). At the time of this publication, ECOG 3311 is published in abstract form 123 with a median follow-up of 31.8 months and suggests that 50 Gy may be sufficient for such patients.…”
Section: Topic 5: Resected P16-positive (Hpv-mediated) Squamous Celmentioning
confidence: 99%